ICTS to improve listening and oral skills in english language learning in higher education (Revista Científica Tecnológica - ISSN: 2708-7093, 2024)
The main objective of this qualitative study of non-experimental design was to analyze the usefulness of Information and Communication Technologies (ICT) to develop oral and listening skills in learning the English language in higher education. The research, carried out under the interpretive paradigm and with a qualitative approach, was carried out with a sample of 30 students from the fourth year of the English major at UNAN-CUR Matagalpa. The survey, questionnaire and observation guide were used as instruments, and observation, interview and survey were used as main techniques, which made it possible to identify, describe and evaluate the importance of the ICT media and resources used to develop communicative competencies. (oral and auditory) in the English language. The results revealed that, although almost all of the participants have electronic devices, there is no evidence of adequate use of them for learning purposes. Likewise, the importance of guaranteeing access to the Internet and technological resources in university classrooms is highlighted to facilitate teaching-learning processes mediated by ICT. However, the mere availability of basic technological resources does not necessarily imply their optimal use by teachers. In this sense, the success of ICT strategies depends on contextual factors and the level of mastery and expertise of both teachers and students, and the technology must be subject to the relevant pedagogical and didactic considerations for its correct implementation in the educational field.
Keywords: ICTS; english; listening skills; oral skills